Cognitive Ability of Students in the Learning Process of Christian Religious Education Using a Scientific Approach at Budi Murni 2 Medan Catholic Private Senior High School - Ermina Waruwu; Din Oloan Sihotang; Johannes Sohirimon Lumbanbatu; Viyanda Mezaluna Br Ginting (International Journal of Scientific Multidisciplinary Research, 2023)
This study aims to answer research questions regarding cognitive ability of students in the learning process of christian religious education using a scientific approach at Budi Murni 2 Medan Catholic Private Senior High School.This study uses a descriptive qualitative approach. The research is carried out at Budi Murni 2 Medan Catholic Private Senior High School from February to April 2023. The informants identified in this study are 11 informants consisting of catholic religious education teachers, vice principals, and students. Data analysis is performed by reducing data, presenting data, and drawing research conclusions. The results of the study show that the process of learning catholic religious education using a scientific approach supports the liveliness of learning activities. The school provides study and learning facilities, such as laptops, projectors, catholic religious education books, and manners for students. The cognitive abilities of students in the learning process of learning catholic religious at Budi Murni 2 Medan Catholic Private Senior High School have been known to have cognitive skills in each student in learning which has begun to increase